POPULISME SEBAGAI BENTUK POLITIK PERTAHANAN PEMIMPIN LOKAL - Haboddin, Mochtar (JPW (Jurnal Politik Walisongo), 2019)
The purpose of this article was to see how local leaders use populist policies to gain political support and maintain their power. This populist policy could be seen from the workings of several local leaders such as Jokowi while leading Jakarta and Solo, Risma in Surabaya, Ridwan Kamil in Bandung and others. To see the extent to which local leaders apply populist policy, this article used a literature-based qualitative research method and used the theory of populist leadership style as an analysis knife. Described from this article that local leaders would use populist policies in an effort to maintain power. In maintaining this power, a populist policy was needed as a strategic way to build the legitimacy of its power in the eyes of the public and politicians in parliament.